A Novel Thiolated Hyaluronic acid Hydrogel for Spinal Cord Injury Repair - Li, Ruifu (Université d'Ottawa / University of Ottawa, 2014)
Spinal Cord Injury (SCI) often causes cell death, demyelination, axonal degeneration and cavitation, resulting in functional motor and sensory loss below the site of injury. In an attempt to overcome SCI, the regenerating neurons require a permissive environment to promote their ability to reconnect. We report a novel thiolated hyaluronic acid (HA) hydrogel scaffold that can be used to repair the injured spinal cord. More specifically, thiolated hyaluronic acid hydrogels with varying thiol concentrations were successfully synthesized. The amount of thiol groups was measured spectrophotometrically using Ellman’s test. HA gels with different crosslinking densities were synthesized and the water content of the hydrogels was determined. The thermal behavior of the HA gels were studied by DSC. The strength of the hydrogels with varying thiol group content was evaluated by a rheometer. In addition, in vitro enzymatic degradation was performed through submerge the hydrogels in 200U/ml of hyaluronidase solution and incubate at 37°C. According to the result of the present study, this novel hydrogel shows great potential to serve as a 3D cell-patterning scaffold which can be inserted into a hollow fiber channel that could be used to promote regeneration after the SCI.
Keywords: Hyaluronic acid; Spinal cord injury